Teologi Ibadah dan Spiritualitas Generasi Milenial : Worship Theology and Spirituality of the Millennial Generation - Amelia Rumbiak (Sekolah Tinggi Teologi Satyabhakti, Malang)
Discourse about millennial generation and religious campaigns has become a worldwide spotlight in various sectors of life. Their existence is the best commodity in human history. In addition, technological advances through the internet are very binding on them so that the millennial generation is a group that grows and is familiar also dependent on gadget technology that masters social media as their new religion. The Church as a Treaty for implementing theology. Warnings and solutions to solutions from Marva J. Dawn and related liturgical figures also support the role of orthodoxy, orthopraxis, and orthopathy from Worship Theology to hold its missiological responsibilities reversed with the help of contemporary worship. ===== Diskursus tentang generasi milenial dan persoalan keagamaan telah menjadi sorotan mendunia dalam berbagai sektor hidup. Keberadaan angkatan mereka menjadi komoditi penting saat ini dan ke depannya. Di samping itu, kemajuan teknologi lewat jaringan internet sangat mengikat mereka sehingga generasi milenial adalah sebuah kelompok yang tumbuh dan akrab serta tergantung dengan teknologi gadget yang menTuan-kan media sosial sebagai agama baru mereka. Gereja sebagai konteks pelaksanaan Teologi Ibadah menghadapi kondisi ini. Peringatan dan rekonstruksi solusi dari Marva J. Dawn dan tokoh-tokoh liturgis lainnya turut menunjukkan pentingnya peran ortodoksi, ortopraksis dan ortopati dari Teologi Ibadah untuk menunjukkan tanggung jawab misiologisnya yang bersifat upside-down melalui ibadah kekinian.